Challenging Entrenched Marital Power in South Africa - Arekapudi, Nisha (World Bank, Washington, DC, 2022)
This brief examines more than thirty years of legal reform aimed at removing husbands’ marital power at the expense of their wives from South African legislation. For decades, marital power relegated wives to a position akin to minors, with devastating effects on women’s economic empowerment. Removing the many components of this form of discrimination from national law has required not only a conducive political environment, but also sustained momentum from the women’s rights movement and selective, strategic litigation that challenges the varied effects. Such reforms have directly and positively affected women’s economic inclusion. While efforts to improve gender equality in South Africa are ongoing, the analysis offers important insights on optimal contexts for change, the role women play in advocacy efforts, and the benefits of reform for economic growth.